The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fpls.2021.762067
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Modification of KNAT7 Transcription Factor Expression Enhances Saccharification and Reduces Recalcitrance of Woody Biomass in Poplars

Abstract: The precise role of KNAT7 transcription factors (TFs) in regulating secondary cell wall (SCW) biosynthesis in poplars has remained unknown, while our understanding of KNAT7 functions in other plants is continuously evolving. To study the impact of genetic modifications of homologous and heterologous KNAT7 gene expression on SCW formation in transgenic poplars, we prepared poplar KNAT7 (PtKNAT7) overexpression (PtKNAT7-OE) and antisense suppression (PtKNAT7-AS) vector constructs for the generation of transgenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In a recent study performed in our laboratory by Ahlawat et al [17], transgenic poplar plants overexpressing PtKNAT7 and AtKNAT7 genes showed enhanced expression of the SCW genes CesA8, IRX9, PAL, and CCR, and reduced expression of the same genes in the poplar PtKNAT7 antisense plants. These results further suggested a positive regulatory role of KNAT7 in SCW formation in poplars.…”
Section: Ptknat7mentioning
confidence: 86%
See 4 more Smart Citations
“…In a recent study performed in our laboratory by Ahlawat et al [17], transgenic poplar plants overexpressing PtKNAT7 and AtKNAT7 genes showed enhanced expression of the SCW genes CesA8, IRX9, PAL, and CCR, and reduced expression of the same genes in the poplar PtKNAT7 antisense plants. These results further suggested a positive regulatory role of KNAT7 in SCW formation in poplars.…”
Section: Ptknat7mentioning
confidence: 86%
“…Furthermore, a detailed investigation into the regulatory network and downstream targets of Class II KNOX TF proteins is required to understand the transcriptional regulation of SCW formation. These studies will help us to modify cell wall formation in transgenic plants and enhance saccharification, as we recently showed [14,17]. Our understanding of the molecular controls of the deposition of each call wall component will help us to design cell walls for improved biomass production and reduced recalcitrance to bioconversion to ethanol.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 89%
See 3 more Smart Citations